Social Stigma in Children with Long COVID - Danilo Buonsenso; Anna Camporesi; Rosa Morello; Cristina De Rose; Matteo Fracasso; Daniela Pia Rosaria Chieffo; Piero Valentini (MDPI AG, 2023)
There is growing evidence that adults with Long COVID suffer from different sets of stigmata related to their condition. In children with Long COVID, this aspect has never been investigated. This study aims to investigate if children with Long COVID also experience stigma. Methods: Children with a previous SARS-CoV-2 infection evaluated at 3 month follow-ups in a pediatric post COVID unit were asked to fill in an online Long COVID Stigma Scale survey before they were assessed by a pediatrician. Doctors were unaware of children's responses when they performed a diagnosis of Long COVID or full recovery from previous infection, according to the World Health Organization definition of pediatric Long COVID. Responses to the Stigma scale were then compared in the two cohorts of children. Results: 224 patients responded to the questionnaire; 40 patients were diagnosed with Long COVID. Children with Long COVID significantly more frequently felt embarrassed about having Long COVID (p 0.035), felt embarrassed about having physical limitations (p < 0.001), felt they were valued less due to Long COVID (p 0.003), felt they were different from other peers due to Long COVID (p 0.033), felt significantly more frequently that people behaved differently towards them because they might be lying since the diagnosis of Long COVID (p 0.006), that they were less respected by others due to Long COVID (p 0.017), that other people thought that Long COVID is not a real disease (p 0.007), that other people thought that developing Long COVID is a sign of weakness (p 0.008), and that other people might judge them negatively due to their diagnosis of Long COVID (p < 0.001). Conclusions: Children with Long COVID, similar to adults, are suffering from stigmata due to their condition,. These data may have implication and should be used by the public, policy makers, and healthcare professionals regarding pediatric Long COVID.